Matching Observed Public Route Choice Data to a GIS Network - Anderson, Marie K.; Rasmussen, Thomas K. (Proceedings from the Annual Transport Conference at Aalborg University, 2010)
This paper is motivated by a growing interest in providing insight into route choices of public transport users. Observations on route choices are collected in the Danish National Travel Survey (Transportvaneundersøgelsen, TU) where respondents describe their chosen route (e.g., modes, times, origins, destinations). In this paper methods are developed to match these data to a GIS network in order to be able to compare the observed routes with routes generated by means of a GIS application. The GIS network is a schedule-based public transport network containing addresses, train stations, bus stops, transfers, train lines, bus lines and a road network. The method developed is able to identify the train stations used, identify the bus stops used, map observations onto relevant links with knowledge of line used and points travelled through (origin, bus stops, train stations, and destination).